在等式y=ax²-bx+c中,
当x=-1时,y=4;
a*(-1)²-b*(-1)+c=4
a+b+c=4 (1)
当x=2时,y=4;
a*2²-b*2+c=4
4a-2b+c=4 (2)
当x=1时,y=2.
a*1²-b*1+c=2
a-b+c=2 (3)
由(1)-(3)得
2b=2
b=1
a=1
c=2
y=ax²-bx+c
y=x²-x+2
当x=-2时,
y=(-2)²-(-2)+2=8
解1由当x=-1时,y=4;当x=2时,y=4;当x=1时,y=2
即得a+b+c=4............①
4a-2b+c=4............②
a-b+c=2............③
由③-②得-2b=-2
即b=1
由①和②得
a+c=3
4a+c=6
解得a=1,c=2
即a=1,b=1,c=2
2由1知
y=ax²-bx+c
=x²-x+2
当x=-2时
y=(-2)²-(-2)+2
=8
在等式y=ax²-bx+c中,当x=-1时,y=4;当x=2时,y=4;当x=1时,y=2. (1)求a、b、c、的值。(2)当x=-2时,求y的值。
解:(1)将三个点得坐标代入等式得:
a+b+c=4........(1);4a-2b+c=4........(2);a-b+c=2.........(3)
(1)-(3)得2b=2,故b=1;代入(1)式得a+c=3,即c=3-a;代入(2)式得4a-2+3-a=3a+1=4,故a=1;
c=4-a-b=4-1-1=2;即a=1,b=1,c=2 ;y=x²-x+2;
(2)。 y(-2)=(-2)²-(-2)+2=4+2+2=8.即x=-2时y=8.